Analisis Hubungan Kualitas Air Terhadap Komunitas Zooplankton dan Ikan di Danau Hanjalutung - Tania Serezova Augusta (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2014)
This study aimed to analyze the quality of water and its relationship with zooplankton and fish communities. This study was conducted over ten (10) months, starting from December 2013 until September 2014 in Hanjalutung Lake. Zoopankton sampling done 2 times with 3 repetitions along with measurements of water quality. Methods used in this research is the method for sampling of zooplankton and fish and measurements of the parameters of physics, chemistry and biology, that are depth, brightness, temperature, pH, dissolved oxygen (DO), and chlorophyll-a. These results showed that the water condition is still in the range that can be tolerated by zoopankton and fish. This study found 21 species of fishes, which dominated by Cyprinidae. Abundance of fish ranged from 1 – 335 fish. Diversity index ranged from 0 – 2 (moderate criteria), uniformity index ranges from 0 – 0,969 (the spread of individuals relatively evenly), and dominance index ranged from 0,222 – 0,763 (low dominance). The most zooplankton were phylum of Rotifera with abundance ranged from 8 – 256 ind/liter. Zooplankton diversity index ranged from 0,462 – 1,816 which allegedly communities were relatively stable during the observation, while the uniformity index ranged from 0,333 to 1 which indicates that the distribution of individuals among species occur relatively evenly and not domination. Water quality during the observation is still in the range that can be tolerated by zooplankton and fish in the Lake hanjalutung. Key words : Water quality, zooplankton community, fish community